PERAN KEPALA DESA MENINGKATAN PARTISIPASI ANGGOTA USAHA EKONOMI DESA SIMPAN PINJAM (UED-SP) MEKAR MAJU DI DESA TANJUNG MEDANG KECAMATAN RUPAT UTARA KABUPATEN BENGKALIS TAHUN 2012-2015 - Azi Safitri; M. Y. Tiyas Tinov (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The role of the village head is as a motivator and community mobilizer; Facilitators, planners, implementers, controllers, supervisors and tutors; And mediators between communities and governments. The role of Village Head to increase community participation is part of efforts to accelerate the level of community welfare development in Tanjung Medang Village.The purpose of this study is to: (1) Know the factors that cause low level of participation activities of members of Economic Enterprises Savings and Savings Village Forward; (2) Describe the Village Head's Role to Increase the Participation of Members of the Savings and Borrowed Country-Owned Economic Enterprises in Tanjung Medang Village. This research uses qualitative research method with descriptive research type, which can be interpreted as problem solving process which is investigated by describing the state of research subject based on facts that appear during the research which then continued with based on the existing theories. Data analysis is done by data reduction, data presentation, and conclusion or verification. The subjects of this study were the Village Head, the Chairman of the Village Consultative Board (BPD), the UED-SP Mekar Maju management, the Village Assistant, the Community Leader and the UED-SP Mekar Maju Member.Based on the results of this study concluded that with the role of village head then the level of public participation in activities UED-SP Mekar Maju in Tanjung Medang Village is increasing. But the fact that the participation of the less active community is caused by several factors, namely the mindset of the community is a factor that influences the progress of UED-SP Mekar Maju, a closed or passive mindset is a factor that hampers public participation in UED-SP Mekar Maju program. Inhibiting factors in the role of village heads to the community: lack of cooperation or coordination between village and village heads, village heads who are less sociable with communities and communities who are less concerned with the environment.Keywords: Role, Village Head, Community Participation